Studi Fatwa Majelis Tafsir Al-Qur'an Menggunakan Hermeneutika Negosiatif - Dini Arifah Nihayati (IAIN Ponorogo, 2023)
AbstractMTAâ€™s fatwa regarding the permissibility of menstruating woman to read the Qurâ€™an on the basic of the QS. Al-WÄqi'ah: 79 contradicts the fatwa of previous scholars which uses the same basis and contradicts the thinking of the majority of society. From this problem, it apperas that MTA as a literal group has produced a liberal fatwa. Liberalism is synonymous with the belief that the original Al-Qur'an only exists in Lawh Al-Mahfudz. This kind of belief is in line with MTA's understanding of the word Al-Muthohharun (holy people) in QS. AL-Waqi'ah: 79. According to their interpretation, this word only applies to angels as intermediaries for the descent of the Qur'an. So that menstruating women are allowed to read the Qur'an because there is no explicit argument against it. This opinion shows freedom in concluding the meaning of the verse by relying solely on reason. for this reason, the author examines it more deeply into a thesis. Negotiative hermeneutics is used as an approach because it has implication for balancing the dialegical relationship of hermeneutics elements and keep the reader away from the result of authoritarian interpretations. The main issues that will be examined are as follows: 1. Why does the MTA as a literal religious institution offer a liberal fatwa by allowing menstruating woman to read the Qurâ€™an? 2. How is negotiative hermeneutics analysis of the MTA fatwa regarding the ability of menstruating woman to read the Qurâ€™an? The author conducts library research. The author collects data using documents. The author analyzes the data inductively by organizing and describing the data, than synthesizes using negotiative hermeneutics and makes conclusions. From this research, it can be concluded that MTA is trapped in a takwil wic is not accordance with the takwil rules and exercises freedom of tought. In terms of negotiative hermeneutics, The MTA fatwa is an authoritarian one. Because MTA still dominates the elements of interpretation, wich result in the neglect of Godâ€™s authority.Â AbstrakFatwa MTA tentang kebolehan wanita haid membaca Al-Qurâ€™an dengan dasar QS. Al-WÄqiâ€™ah:79 berseberangan dengan fatwa ulama terdahulu yang menggunakan dasar yang sama. Masalah tersebut mengakibatkan fatwa MTA dinilai bertentangan dengan pemikiran mayoritas masyarakat dan muncul dugaan bahwa MTA sebagai kelompok literalis telah menghasilkan fatwa liberal. Liberal identik dengan keyakinan bahwa Al-Qurâ€™an asli hanya ada di Lauh Al-Mahfudz. Keyakinan semacam ini senada dengan pemahaman MTA terhadap kata Al-Muthohharun (orang-orang yang suci) dalam QS. AL-Waqiâ€™ah: 79. Menurut penafsiran mereka, kata tersebut hanya berlaku bagi malaikat sebagai perantara turunnya Al-Qurâ€™an. Sehingga wanita haid diperbolehkan membaca Al-Qurâ€™an karena tidak ada dalil eksplisit yang melarangnya. Pendapat ini menunjukkan kebebasan dalam menyimpulkan maksud dari ayat tersebut dengan mengandalkan akal semata. Untuk itu, penulis mengkajinya lebih dalam. Hermeneutika negosiatif digunakan sebagai pendekatan karena berimplikasi pada keseimbangan hubungan dialektis komponen hermeneutika dan menghindarkan pembaca dari hasil penafsiran otoriter. Pokok permasalahan yang akan dikaji sebagai berikut: 1. Mengapa MTA sebagai lembaga keagamaan yang literalis menwarakan fatwa liberal dengan memperbolehkan wanita haidh membaca Al-Qurâ€™an? 2. Bagaimana analisis hermeneutika negosiatif Abou El Fadl terhadap fatwa MTA tentang kebolehan wanita haidh membaca Al-Qurâ€™an? Penulis mengumpulkan data menggunakan dokumen. Penulis menganalisa data secara induktif dengan mengorganisasikan dan mendeskripsikan data, kemudian melakukan sintesa menggunakan hermeneutika negosiatif dan membuat kesimpulan. Penulis menghasilkan kesimpulan bahwa MTA terjebak dalam upaya takwil namun tidak sesuai dengan kaidah takwil dan melakukan kebebasan berfikir. Dalam kacamata hermeneutika negosiatif, fatwa MTA tergolog otoriter. MTA sebagai pembaca masih medominasi unsur-unsur penafsiran, yang mengakibatkan pengabaian otoritas Tuhan.